Prolactin and Dehydroepiandrosterone Levels in Women with Systemic Lupus Erythematosus: The Role of the Extrapituitary Prolactin Promoter Polymorphism at −1149G/T - Treadwell, Edward L.; Wiley, Kenneth; Word, Beverly; Melchior, William; Tolleson, William H.; Gopee, Neera; Hammons, George; Lyn-Cook, Beverly D. (My University, 2015)
Systemic lupus erythematosus (SLE) has shown an association with high levels of prolactin, low levels of dehydroepiandrosterone (DHEA), and induction of inflammatory cytokines in the serum of patients with the disease. This preliminary study examined the relevance of a −1149G/T functional single-nucleotide polymorphism (SNP) (rs1341239) in the promoter of the extrapituitary prolactin gene in a cohort of African American and European American women with lupus. Examination of this SNP revealed that the −1149TT genotype was correlated with higher levels of prolactin in serum and prolactin gene expression (p = 0.0001) in peripheral blood mononuclear cells (PBMCs). Lower levels of DHEA in serum were demonstrated in lupus patients (p = 0.001); those with the −1149TT genotype had the lowest levels of DHEA. Furthermore, a small subset of women who were on DHEA therapy and had a TT genotype showed a significant decrease in prolactin gene expression and lower disease activity scores (SLEDAI). Lupus patients, particularly African Americans, had significantly higher levels of IL-6 (p = 0.0001) and TNF-α (p = 0.042). This study suggests that the −1149TT genotype may be a risk factor for lupus and may predict who could possibly benefit from DHEA therapy; therefore, these results should be validated in a larger cohort with all ethnic groups.